Unveiling maker mindsets: a journey of formation and transformation through design thinking-making pedagogy within a lesson study context - Li, Jiajia; Goei, Suilin; Huang, Rongjin (Frontiers in Education, 2024)
Maker Education (ME) focuses on fostering students' Maker Mindsets (MM). However, prevailing ME practices often lack a structured approach, that impedes the effective development of students' MM. To address this challenge, a Design Thinking-making pedagogy (DTMP) is used to design ME lessons through a three-month Lesson Study (LS) cycle. Employing a qualitative multiple case study methodology, we studied the development and transformation of MM in three elementary school students. Diverse data were collected, including student artefacts, video recordings of teacher discussions, and audio recordings of the interviews. The findings revealed common cognitive, selfefficacy, and collaboration improvements among the three students. Unique changes in individual cognitive skills, motivational patterns, and obstacles to collaboration were also observed. Furthermore, key factors influencing MM development were identified across individual, social, and pedagogical dimensions. Individual factors included prior knowledge, maker skills, and motivation, whereas social factors included teachers' attitudes, recognition, feedback, and peer collaboration.Pedagogical practices, such as project difficulty, structure, and authenticity, play a crucial role in MM development. This study not only contributes valuable insights into MM development, but also underscores the pivotal role of tailored, personal real-life experiences in ME pedagogy. Furthermore, our study suggests that teachers can enhance ME pedagogy by intentionally designing it to facilitate MM in students, using the LS approach.